Advanced Sentiment Analysis Using Deep Learning: A Comprehensive Framework for High-Accuracy and Interpretable Models - Amrullah, Ata (Intellithings Journal, 2025)
Sentiment analysis has become a critical tool for understanding public opinion, customer feedback, and social media trends. Despite significant advancements in deep learning, existing models often struggle with accuracy, generalizability, and interpretability, particularly when applied to complex and noisy datasets. In this paper, we propose a novel deep learning framework for sentiment analysis that addresses these limitations by combining the strengths of convolutional neural networks (CNNs) and transformer-based architectures. Our framework leverages verified and high-quality datasets, including Twitter Sentiment140, IMDb movie reviews, and Amazon product reviews, to ensure robustness and reliability. We introduce a hybrid model that integrates multi-head attention mechanisms with hierarchical feature extraction, enabling the model to capture both local and global contextual information effectively. Additionally, we employ state-of-the-art interpretability techniques, such as SHAP and LIME, to provide transparent and human-understandable explanations for model predictions. Experimental results demonstrate that our framework achieves superior performance compared to existing state-of-the-art methods, with an accuracy of 94.3%, an F1-score of 93.8%, and an AUC-ROC score of 97.2%. Furthermore, our model's interpretability features offer valuable insights into decision-making processes, making it highly applicable for real-world applications such as brand monitoring, market analysis, and political sentiment tracking. This study not only advances the field of sentiment analysis but also provides a scalable and interpretable solution for future research in natural language processing.